Effect of Cold Rolling and Cryogenic Treatment on the Microstructure and Mechanical Properties of Fe–32Ni Alloy - Dongyun Sun; Jianguang Li; Xiaohong Hao; Mingming Wang; Dongdong Li; Xiaowen Sun; Zhinan Yang; Tiansheng Wang; Fucheng Zhang (Metals, 2024)
In this work, the effects of cold rolling (CR) and cold rolling–cryogenic treatment (CR–CT) on the microstructure and mechanical properties of Fe–32Ni alloy were studied via optical microscopy methods, OM, SEM, XRD, TEM, tensile strength and hardness tester, and tensile testing. The results reveal the grain refinement in the alloy after rolling deformation. When the deformation is higher than 85%, the polygonal austenite grains become layered, and a small amount of martensite forms. Because of the inhibitory effect of cold-rolling deformation before cryogenic treatment on martensitic transformation, the amount of martensite form phase after cryogenic treatment decreases with the increase of deformation. The hardness and strength of the sample, independent of whether the cryogenic treatment is performed, increase with the increase of deformation degree. Under the same deformation rate, the hardness of the CR–CT sample is higher than that of the CR sample, which is related to the hard martensite phase with high dislocation density obtained during cryogenic treatment. The strain hardening behavior of the sample is greatly affected by the deformation degree. With the increase of true strain, the work hardening exponent of CR and CR–CT samples undergoing severe plastic deformation is lower than that at small deformation degree and low dislocation density, which is attributed to the earlier entanglement of high dislocations in CR and CR–CT samples with large deformation degrees.